Development of Fermented Pork (Nham) Processes using Starter Culture - Yodin, Kanokwan; Treesuwan, Khemmapas (Rajamangala University of Technology Tawan-ok Research Journal, 2024)
This study aimed to enhance the quality and consistency of fermented pork production by employing starter cultures. Pediococcus acidilactici and Pediococcus pentosaceus were selected as starter cultures to improve the product's sensory properties and safety. Optimal fermentation conditions were determined by varying the initial bacterial concentration and fermentation time. The results indicated that a combination of the two LAB strains, with an initial concentration of 1% (v/w) and a fermentation period of 2 days, yielded sausage with the best flavor, aroma, and texture. Furthermore, the product exhibited excellent stability when stored at 4°C for 45 days. This study demonstrates the potential of using specific LAB strains to improve the quality and shelf life of fermented pork sausage, providing a foundation for standardized and safe production.